Digital Marketing Vokafe dalam Membangun Brand Awareness dan Minat Beli Mahasiswa di Sekolah Vokasi IPB - Hervina Afrianti Rahayu; Aceng Hidayat (Jurnal EMT KITA, 2026)
Brand awareness is the initial stage before the emergence of purchasing interest. Digital marketing plays a role in building brand awareness. This study aims to analyze Vokafe's digital marketing strategy in building brand awareness and purchasing interest among students at the IPB Vocational School. This study uses a descriptive qualitative approach. Data were obtained through in-depth interviews consisting of one manager and four students as informants, participant observation, documentation, and literature studies, using source triangulation to ensure the credibility of the findings. The results show that the digital marketing strategy through Instagram contributed to increasing Vokafe's brand exposure, marked by a 2,780% growth in followers (from 5 to 144 followers) and an increase in insight to reach 5.3 thousand. The implementation of Integrated Marketing Communication (IMC) through advertising, public relations, sales promotion, personal selling, and direct marketing was able to build student brand awareness to the brand recall stage. This brand awareness develops into purchasing interest shown through information searches, purchases, repeat purchases, and recommendations to others according to the AISAS (Attention, Interest, Search, Action, Share) model stages. This study concludes that strengthening content consistency, sales promotions, and digital interactions is necessary to push Vokafe to reach top of mind.